HUBUNGAN KEBUGARAN JASMANI DENGAN TINGKAT KECEPATAN TENDANGAN SABIT PESERTA EKSTRAKULIKULER PENCAK SILAT MA PSA NURUL AMAL BANDUNGAN KABUPATEN SEMARANG - Trisyono; Catur Wahyu Priyanto; Lusiana; Muhlis (JURNAL ILMIAH PENJAS (Penelitian, Pendidikan dan Pengajaran), 2023)
The purpose of this research was to examine the correlation between physical fitness and the speed of the sickle kick in the sport of pencak silat in the extracurricular activities of MA PSA Nurul Amal Bandungan in 2022 . The research object that has been used in this study is limited to pencaksilat extracurricular participants at MA PSA Nurul Amal Bandungan Semarang Regency in 2022. The research sample were 10. The research method that has been used in this research is the correlation method with physical fitness ability test techniques and using evaluator sheets. In the research, impact of physical fitness on the speed of the sickle kick is 49.7%, which is obtained from the partial correlation coefficient for physical fitness (0.49.7 x 100%). The results of this analysis indicate that extracurricular participants who have good physical fitness will be able to perform sickle kicks faster than participants who have poor physical fitness. And the rest is influenced by other reasons not examined in this research.